Domestic violence against a woman in Reynosa, Tamaulipas, Mexico - Villarreal-Sotelo , Karla (Universidad Autónoma de Tamaulipas, 2009)
This research is related to domestic violence, the ways of this problematic occurs and its persistence inside of homes of our city. The study is focusing on women victimization and types of violence, the offenders, the origins of this problem and the factors that contribute on the prevalence of this social problem, also, violence effects, legal parameters and institucions that give support to the victims. As a result of this study, the physical violence is the most common type of agression that is denunced, it is 45% of the cases. In the most of the cases, the agressor is part of the home or was part of it. It can be, the husband or the partner, whom were the principal agressors. The average of the agressors ages is between 25 and 29 years old. It is remarkable that in Reynosa, the 90% of the denounces are from women that no belong to our community. These women are from states located on South of Mexico.